Learning from a mountain: Interview with Bruce Clarkson - Clarkson, B.; McDonald, Tein (Wiley-Blackwell Publishing Ltd, 2014)
Bruce Clarkson is recognised as one of New Zealand's foremost authorities on ecological restoration, with a research and management focus on restoring indigenous vegetation communities in cities. He urges optimism in the face of change, by emphasising the importance of long-term and broad-scale perspectives. © 2014 Ecological Society of Australia.